Persistent opioid use after radiation therapy in opioid-naive cervical cancer survivors. Issue 7 (September 2019) - Ward, Kelsey; Ramzan, Amin; Sheeder, Jeanelle; Fischer, Stacy; Lefkowits, Carolyn
Abstract : Objectives: Opioids are first-line therapy for cancer-related pain, but their use should be minimized in disease-free survivors. We sought to describe rates and identify predictors of persistent opioid use among previously opioid-naive cervical cancer survivors treated with radiation. Methods: Opioid-naive cervical cancer patients treated primarily with radiation and chemosensitization at a single institution, between January 2011 and December 2015, were identified. Charts were reviewed for demographics, disease, and treatment characteristics, and opioid prescriptions. Primary outcome was persistent opioid use, defined as continued opioid prescription use, 6 months after radiation; patients recurring within 6 months were excluded. Groups were compared using χ 2 or Fisher's exact test. Multivariable logistic regression identified predictors of persistent opioid use. Results: A total of 96 patients were included, with a median age of 49 years (range 27–84). Most patients (59%) at diagnosis had International Federation of Gynecology and Obstetrics (FIGO) stage I or II cervical cancer. The most common histology was squamous cell carcinoma (72%) and most (94.7%) patients received radiation with chemosensitization. Rates of persistent opioid use at 3 and 6 months after treatment were 29% and 25%, respectively. Persistent users were more likely to be <40 years old, have disease outside the pelvis at diagnosis, and have had a history of substance abuse, depression or anxiety (p<0.05). In multivariable analysis, a history of substance abuse (adjusted OR 6.21, 95% CI 1.08 to 35.67) and depression or anxiety (aOR 6.28, 95% CI 1.70 to 23.30) were independently associated with persistent opioid use. Conclusion: Our study showed that 25% of patients with cervical cancer were still using opioids 6 months after radiation. History of substance abuse and depression or anxiety, all known risk factors for opioid misuse, were associated with persistent use. The goal in the disease-free survivor population should be opioid independence.